PENGARUH SINERGI PEMASARAN DAN SINERGI TEKNOLOGI TERHADAP KINERJA PRODUK BARU PADA ERA DAN POST PANDEMI - Muhafidhah Novie (GREENOMIKA, 2020)
This study aims to determine (1) the effect of marketing synergy and technology synergy on the performance of new products during the pandemic (2) the influence of technology synergy on the performance of new products during the pandemic (3) between marketing synergy and which technology synergy suggests a greater influence on new product performance. The sample in this study were MSME-based food and beverage businesses that are members of the Sidoarjo Food and Beverage Association. The research method used is quantitative research methods using SPSS 22 tools, as an analysis tool. The results of the analysis suggest that (1) marketing synergy can improve the performance of new products (2) technology synergy has a positive effect on the performance of new products (3) the results of the regression equation suggest that technology synergy has a greater influence than marketing synergy on the performance of new products.